Chinese investment in Ghana’s manufacturing sector - Tang, Xiaoyang (International Food Policy Research Institute, 2017)
This paper uses Ghana as a case study to illustrate the extent to which Chinese manufacturing firms are driving manufacturing in an African country. Through a combination of desktop and field research, the author finds that the total number of Chinese manufacturing investments in Ghana indeed increased during past decade, but quite a few projects have been abandoned or not implemented because of the unfavorable investment environment. Small and large manufacturing projects can be found in different sectors, such as plastics, steel, pharmaceuticals, and others. All of the manufacturing investments target local or regional markets, either taking advantage of local raw materials or seeing opportunities in a market with little competition. Transitioning from trading to manufacturing investment and clustering are identified as the main patterns by which Chinese investors establish themselves in Ghana. Chinese firms source simple raw materials from local suppliers but import industrial supplies from abroad. Learning from Chinese business models, a few local businessmen have started their own manufacturing projects, mostly in the plastics recycling sector, but a lack of capital appears to keep some local players from moving up the value chain. Ghana’s weak economy itself is limiting technology transfer and local linkages between Chinese firms and Ghanaians.